2022
DOI: 10.1029/2022gl098708
|View full text |Cite
|
Sign up to set email alerts
|

The Oscillatory Motion of Jupiter's Polar Cyclones Results From Vorticity Dynamics

Abstract: The poles of Jupiter were observed in detail for the first time by the Juno spacecraft in 2016 (Bolton et al., 2017). In contrast with the polar regions of Saturn, which are inhabited by a single polar cyclone (PC) (Baines et al., 2009;Sánchez-Lavega et al., 2006), Jupiter's PCs are surrounded by a ring of stable circumpolar cyclones (CPCs) (Adriani et al., 2018;Orton et al., 2017). There are eight CPCs at the north pole and five at the south (Figure 1), each with a diameter of roughly 5,000 km and velocities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Another crucial issue awaiting theoretical descriptions is the hydrodynamic interactions among closely located convective vortices that give rise to the long-range collective motion of the vortices. What are the implications of the vortex dynamics presented in this study for the correlated vortex motion observed in giant gaseous planets and other large-scale geophysical and astrophysical flows (Li et al 2020;Gavriel & Kaspi 2021, 2022Mura et al 2021)? We expect future progress in answering these questions.…”
Section: Summary and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Another crucial issue awaiting theoretical descriptions is the hydrodynamic interactions among closely located convective vortices that give rise to the long-range collective motion of the vortices. What are the implications of the vortex dynamics presented in this study for the correlated vortex motion observed in giant gaseous planets and other large-scale geophysical and astrophysical flows (Li et al 2020;Gavriel & Kaspi 2021, 2022Mura et al 2021)? We expect future progress in answering these questions.…”
Section: Summary and Discussionmentioning
confidence: 89%
“…What are the implications of the vortex dynamics presented in this study for the correlated vortex motion observed in giant gaseous planets and other large-scale geophysical and astrophysical flows (Li et al. 2020; Gavriel & Kaspi 2021, 2022; Mura et al. 2021)?…”
Section: Summary and Discussionmentioning
confidence: 91%
“…Since the discovery of Jupiter's polar cyclones, the role of vorticity gradient forces (or generalized β ‐drift), which takes into account both β and the relative vorticities of all neighboring cyclones, presented a consistent picture. These forces were used to explain the mean latitude of the cyclones and their number (Gavriel & Kaspi, 2021), the oscillatory motion patterns of the cyclones (Gavriel & Kaspi, 2022), and now their mean westward drifts as well. This series of studies, revealing different aspects of these forces, implies that these polar cyclones behave, to leading order, like discrete objects, linearly forced by a “spring‐like” system driving them all in the poleward‐westward direction while pushing them one from another.…”
Section: Discussionmentioning
confidence: 99%
“…(2022); see Figure S3 in Supporting Information for the equivalent north‐pole figure, based on the existing observations). It can be seen (Figure 4a) that the CM's trajectory is indeed very clean, and possesses mostly the 12‐month oscillations exhibited by the individual cyclones (Figures 4d and 4e, Gavriel and Kaspi 2022). This suggests that this 12‐month mode of motion is mostly synchronized between the cyclones, and is therefore largely due to the motion of the CM (i.e., the first mode of motion where all cyclones oscillate together as a group).…”
Section: The Center Of Mass Of the Polar Cyclones In The Observationsmentioning
confidence: 91%
See 1 more Smart Citation